Possible Approach to Esophageal Lung with Long Tracheobronchial Gap - Ichino, Martina; Pugni, Lorenza; Zanini, Andrea; Morandi, Anna; Mosca, Fabio; Macchini, Francesco (European Journal of Pediatric Surgery Reports, 2019)
Esophageal lung is a rare bronchopulmonary foregut malformation characterized by an anomalous origin of one of the main bronchi which arises from the esophagus. Less than 30 cases are reported in the literature. Therefore, there are no standardized guidelines for the treatment of this condition. We report a case of right esophageal lung diagnosed in a neonate. The patient was treated with thoracoscopic closure of the ectopic main bronchus in the neonatal period, followed by delayed pneumonectomy at 5 months of age. No prosthetic substitute was implanted in the ipsilateral hemithorax after pneumonectomy. The patient is now 4 years old and doing well, postpneumonectomy syndrome was never observed. Our strategy and the possible alternatives are discussed here.
Keywords: esophageal lung; pneumonectomy; thoracoscopy